POSSIBLE PARALLELS IN VARIABLE GEOMETRY - Adriana Conti Puorger (Bollettino della Società Geografica Italiana, 2019)
The current paper focuses on the study of the similarity between the development of the Territorial Cooperation, representation of the cohesion’s politics at the European level, and the improving steps on the territorial reorganization that are taking place in Italy. The elaboration of a model of economic politics subjected to the «dictat» of equity and efficiency is indeed constrained by financial issues both at an European level and a national one. Furthermore, the problem of the distribution of the competency is affected from the burden of embracing the mentioned model in the respect of the administrative uniformity. However, such administrative uniformity does not coincide with the regional uniformity, in a geographical aspect, consequently compromising the criterion of the distributive equity. In order to overcome such problem it is needed to find «ad hoc» solutions stemming from the application of the principle of the cohesion. An interesting practical example of that is found in the Macro-Regions. Likewise, at an Italian scale, such principle seems to lead to the approach of the territorial reorganization either via the intercommunal associations or with the simplification of the government levels existing on the territory. Hence, the term «variable geometry» fits both scales and identifies the process of recognition of the institutional duties without additional tax raises. The analysis of what is happening at the macro-regional dimensional level in Europe and of the territorial reorganization in Italy, it is adopted in the paper as interpretation and evaluation of the enforcement of the principle of cohesion to the territorial dimension adopting a reorganization of the space capable to achieve the optimization of the public resources.